PERBANDINGAN EFEKTIVITAS WILLIAM’S FLEXION EXERCISE DAN MCKENZIE EXERCISE Terhadap Perubahan Nyeri dan Lingkup Gerak Sendi Lumbosakral pada Low Back Pain Mekanik Pasien Tinjauan di RSUD Ulin Banjarmasin Periode 2022 - Pambudi, Zanuba Tarieq Ridho; Hayati, Azka; Noor, Zairin; Siddik, Muhammad; Fakhrurrazy, Fakhrurrazy (Universitas Lambung Mangkurat, 2023)
Low back pain is a pain that is felt in the lower back area, with various variations of the duration of the pain. This pain is localized below the angle of the last rib to the lumbar region, which can cause movement limitations in the lumbosacral joints. The causes of low back pain can be caused by musculoskeletal diseases, psychological disorders, and incorrect mobilization. This study aims to determine the differences in the effectiveness of the william’s flexion exercise and the mckenzie exercise on changes in pain and the range of motion of the lumbosacral joints in mechanical low back pain in review patients at Ulin General Hospital, Banjarmasin. This study used a quasi-experimental research design with a two group pretest-posttest design with an approach through direct observation and interviews with respondents at Ulin Hospital, Banjarmasin, on 23 samples that met the inclusion criteria. The results of this study indicated that there was a decrease in the pain scale (VAS) in group I (william flexion exercise) with a value of p = 0.03 and group II (mckenzie exercise) with p = 0.02, which means there is a significant difference. Whereas in ROM groups I and II the value of p = 0.317 which means there is no significant difference. For differences in the effectiveness of groups I and II, p = 0.795 on VAS and p = 0.606 on ROM, which means there is no significant difference between them.